2014
DOI: 10.3386/w20253
|View full text |Cite
|
Sign up to set email alerts
|

Guns and Votes

Abstract: Why are U.S. congressmen reluctant to support gun control regulations, despite the fact that most Americans are in favor of them? We argue that re-election motives can lead politicians to take a pro-gun stance against the interests of an apathetic majority of the electorate, but in line with the interests of an intense minority. We develop a model of gun control choices in which incumbent politicians are both office and policy motivated, and voters differ in the direction and intensity of their preferences. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
2
11
0
Order By: Relevance
“…The ability of the NRA to bring its members to the voting booth is consistent with Bouton et al. (), who found that timing matters enormously in the NRA's influence: senators (particularly Democratic incumbents) are most likely to shift in a pro‐gun direction in the lead up to a reelection.…”
Section: The Gun Lobby State Legislation and Surges In Gun Salessupporting
confidence: 80%
“…The ability of the NRA to bring its members to the voting booth is consistent with Bouton et al. (), who found that timing matters enormously in the NRA's influence: senators (particularly Democratic incumbents) are most likely to shift in a pro‐gun direction in the lead up to a reelection.…”
Section: The Gun Lobby State Legislation and Surges In Gun Salessupporting
confidence: 80%
“…Bouton, Conconi, Pino, and Zanardi (2013) describe a probabilistic voting model in which politicians may pander to the interests of a vocal minority on an issue which the rest of the electorate cares less intensely about.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Bouton, Conconi, Pino, and Zanardi (2013) and Conconi, Pino, and Zanardi (2013) shows that, when U.S. senators approach reelection, they are more likely to take a pro-gun stance when voting on gun control regulations and a green stance when voting on environmental policies. Like trade, gun control and the environment are "secondary" policy issues, which do not shape the decisions of most voters.…”
mentioning
confidence: 99%
“…Conconi, Facchini, and Zanardi, 2014;Bouton, Conconi, Pino, and Zanardi, 2014;Conconi, Pino, and Zanardi, 2015). Our theoretical model builds on the sequential reciprocity framework developed by Dufwenberg and Kirchsteiger (2004).…”
mentioning
confidence: 99%